Methodology for the organisation of professional training of senior citizens: general concept - T. M. Rezer (Russian State Vocational Pedagogical University, 2021)
Introduction. The process of population aging in modern civilisation is developing at an increasing pace. Russia has not remained aloof from this trend. Intense aging of the population will lead, in particular, to the fact that older people will become a necessary resource for the labour market as well as for the society activity at both macro- and micro-levels. Continuing active employment of senior citizens is a new challenge facing states.The aim of present conceptual article is to theoretically substantiate and to develop approaches for building a model for organisation of senior citizens' professional training (persons from 50 to 70 years old). This type of training requires to be based on andragogy and geronto-gogy principles and to be targeted at continuing of labour activity by this category of population through acquisition of new professional knowledge and competencies.Methodology and research methods. The current research is based on the methodology of system-based analysis of theoretical sources, foreign and Russian pedagogical experience. Interdisciplinary and complex approaches were used to build the concept of the model to organise professional training of senior citizens.Results and scientific novelty. The obtained results allowed the author to conclude that at present stage of the Russian state and Russian society development, there is a need for scientific interdisciplinary knowledge, which substantiates the principles and didactic support of professional training of senior citizens in order to continue their active labour activity and to propose the concept for building the model for the organisation of such training. The conceptual model for the organisation of professional training of senior citizens is developed from the point of system-based approach and includes the following elements: 1) clarification of conceptual apparatus of senior adult education; 2) determination of anatomical and physiological features of senior citizens; 3) argumentation of the need of senior citizens for professional training; 4) determination of the peculiarities of professional training for senior citizens; 5) development of prerequisites list for successful learning of senior citizens; 6) formulation of learning objectives and tasks for its organisation; 7) choice of approaches for building the model of training and its principles as well as methodology for determining the quality and results of training.Practical significance. The proposed concept of the model for the organisation of professional training of senior citizens can be used as a basic concept for further theoretical and practical developments in this field.